Carbohydrate Mouth Rinse and Spray Improve Prolonged Exercise Performance in Recreationally Trained Male College Students - Asako Shirai; Tsuyoshi Wadazumi; Yoko Hirata; Naomi Hamada; Nobuko Hongu (MDPI AG, 2022)
Mouth rinsing with a carbohydrate (CHO) solution has emerged as a sports nutrition strategy to increase endurance performance. This study aimed to clarify the effects of two forms of CHO sensing in the mouth (i.e., CHO mouth rinse (CMR) and CHO mouth spray (CMS)) on exercise performance during prolonged exercise, including ultra-high intensity intermittent exercise over time. We conducted the following experimental trials: (1) 6% glucose solution (G), (2) 6% CMR, (3) 6% CMS, and (4) water (WAT). These trials were conducted at least 1 week apart in a randomized crossover design. Eight male college students performed constant-load exercise for 60 min (intensity 40% VO2peak), four sets of the Wingate test (three 30 s Wingate tests with a 4 min recovery between each test), and a constant-load exercise for 30 min (intensity 40% VO2peak). The mean exercise power output (Watt), ratings of perceived exertion, and blood glucose levels were measured. We found that the mean power values of the CMR and CMS in the third and fourth sets was significantly higher than that of WAT (p < 0.05), and that the G trial did not show a significant difference from any other trial. Thus, when compared to G or WAT, CMR and CMS can help improve endurance exercise performance.